THE RELATIONSHIP BETWEEN HOUSEWIVES' BEHAVIOR IN WASTE MANAGEMENT IN RW 07 PETUKANGAN SELATAN VILLAGE IN 2022 - Syifa Tiara Nabila; Gilang Anugerah Munggaran (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
DKI Jakarta has experienced an increase in waste every year. Currently, waste in DKI Jakarta has reached 7,400 tons/day and in the City of South Jakarta in 2021 it produced 1,937 tons/day and 532,885 tons/year of waste. This research aims to determine the relationship between Housewives' Behavior in Waste Management in RW 07 Petukangan Selatan Village in 2022. This study used quantitative methods with an observational analytical approach, and a cross-sectional study design, using purposive sampling with 100 respondents. The results of this study found no relationship between education and the behavior of housewives p-value (of 0.810) and there was no relationship between attitudes with the behavior of housewives with a p-value (of 0.094), related variables namely knowledge with a p-value (0.007) and infrastructure with p-value (0.008). In this study, it was found that there was no relationship between education and attitudes toward waste management behavior, but there was a relationship between knowledge and infrastructure and waste management behavior. For the community to participate in a series of training activities related to waste management carried out by the government to get knowledge that can be applied to the environment.